Comparison of Slides and Video Clips as Different Methods for Inducing Emotions: An Electroencephalographic Alpha Modulation Study - Romeo, Zaira; Fusina, Francesca; Semenzato, Luca; Bonato, Mario; Angrilli, Alessandro; Spironelli, Chiara (Frontiers in Human Neuroscience, 2022)
Films, compared with emotional static pictures, represent true-to-life dynamic stimuli that are both ecological and effective in inducing an emotional response thanks to multimodal stimulation (i.e., visual and auditory systems). We hypothesized that a direct comparison between this two methods would have shown greater efficacy of movies in eliciting emotions at both subjective and neurophysiological levels. Therefore, we compared these two methods in a group of 40 young adults (20 females). EEG Alpha rhythm (8-12 Hz) was recorded from 64 scalp sites while participants watched two separate blocks of 45 slides and 45 clips. Each block included three groups of 15 validated stimuli classified as Erotic, Neutral and Fear content. Greater self-perceived arousal was found after the presentation of Fear and Erotic clips compared with the same slide categories. sLORETA analysis showed a different lateralization pattern: slides induced decreased Alpha power (greater activation) in the left secondary visual area (Brodmann Area, BA, 18) to Erotic and Fear compared with the Neutral stimuli. Instead, clips elicited reduced Alpha in the homologous right secondary visual area (BA 18) again to both Erotic and Fear contents compared with Neutral ones. Comparison of emotional stimuli showed smaller Alpha power to Erotic than to Fear stimuli in the left precuneus/posterior cingulate cortex (BA 7/31) for the slide condition, and in the left superior parietal lobule (BA 7) for the clip condition. This result matched the parallel analysis of the overlapped Mu rhythm and can be interpreted as Mu/Alpha EEG suppression elicited by greater motor action tendency to erotic (approach motivation) compared to fear (withdrawal motivation) stimuli. Correlation analysis found lower Alpha in the left middle temporal gyrus (BA 21) associated with greater pleasantness to Erotic slides (r38 = -0.62, p = 0.009), whereas lower Alpha in the right supramarginal/angular gyrus (BA 40/39) was associated with greater pleasantness to Neutral clips (r38 = -0.69, p = 0.012). Results point to stronger emotion elicitation of movies vs. slides, but also to a specific involvement of the two hemispheres during emotional processing of slides vs. clips, with a shift from the left to the right associative visual areas.